Firm innovations from voluntary dyadic engagement with nonprofit organisations: an exploratory UK study - Holmes, Sara (Cranfield University, 2010)
This dissertation presents the findings of an exploratory collective case-study examining corporate innovations arising from voluntary dyadic engagement between UK firms and nonprofit organisations (NPOs) focused on social issues. Whilst the extant literature demonstrates that pro-active engagement with NPOs can assist firms innovate, there has been no empirical work which explores the relationship between the engagement and the innovation outcome: a gap which this research addresses. In doing so, it illustrates how concepts and constructs from the innovation management literature can be applied usefully to the stakeholder and cross-sector collaboration field. To date, empirical studies addressing firm-NPO engagements have concentrated overwhelmingly on partnerships to address environmental issues. This study provides insights into cross-sector engagements focused on addressing social issues. Using a form of analytic induction to evaluate qualitative case-data from ten dyadic engagements, this dissertation addresses the question: “how do firms innovate through engagement with social issues nonprofit organisations?” The research found that product and service innovations resulted from engagements where the firm had an external stakeholder orientation and was focused on delivering tangible demonstrations of corporate responsibility. Process innovations, by contrast, were produced from engagements where firms had an internal stakeholder orientation. Two distinctions were noted in the innovation process, too. Firstly, a more exploratory approach to dyadic engagement activities, which resulted in an emergent innovation process; and secondly, a focused and pre-determined search activity to exploit the resources of the nonprofit partner which demonstrated a more planned innovation process. In addition, two distinct boundary spanning roles were identified: in dyads with no direct management involvement in the engagement, the role was associated with formal responsibilities from senior management to „manage‟ innovation opportunities and outcomes. In dyads where senior management were involved, there was no such formality; the boundary spanner acted to „facilitate‟ search and exploration to locate opportunities for innovation through idea exchange. The application of innovation constructs to the business and society field has enabled firm engagement with nonprofit stakeholders to be examined through a new lens and demonstrated how firms innovate from such relationships. In particular it has highlighted the key role played by the firm boundary spanner (relationship manager) and how this role alters depending on senior management involvement: a distinction which has not been made in the extant literature and would benefit from further examination.
Keywords: Firm-nonprofit partnership; stakeholder engagement; social issues; social innovation